2020
DOI: 10.3389/fpsyt.2019.00934
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Behavior, Hostility, and Associated Care Needs in Patients With Psychotic Disorders: A 6-Year Follow-Up Study

Abstract: Background: Hostility and aggressive behavior in patients with psychotic disorders are associated with demographic and clinical risk factors, as well as with childhood adversity and neglect. Care needs are an essential concept in clinical practice; care needs in the domain of safety for others reflect the actual problem the patient has. Hostility, aggressive behavior, and associated care needs, however, are often studied in retrospect.Method: In a sample of 1,119 patients with non-affective psychotic disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
(61 reference statements)
2
13
0
Order By: Relevance
“…First, a 6-year follow-up study of patients with psychotic disorders confirmed earlier studies that childhood trauma is a risk factor for aggression (hazard ratio=1.74, 95% CI=1.03-2.93) (6). Another important and well-known childhood risk factor, conduct disorder, was confirmed in the article by Krakowski et al (1).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…First, a 6-year follow-up study of patients with psychotic disorders confirmed earlier studies that childhood trauma is a risk factor for aggression (hazard ratio=1.74, 95% CI=1.03-2.93) (6). Another important and well-known childhood risk factor, conduct disorder, was confirmed in the article by Krakowski et al (1).…”
supporting
confidence: 66%
“…This relationship was not mediated by substance abuse (10). In more chronic psychotic disorders, 26% of the safety needs related to aggression were attributable to impulsivity 3 years earlier, assuming causality (6).…”
mentioning
confidence: 89%
“…Meta-analytic data from psychotic disorders in general also found excitement associated with violence, but not uncooperativeness (Witt et al, 2013). More recent work found both excitement and uncooperativeness associated with different aggressiveness outcomes, although with differences between these measures (Faay et al, 2020). Compared with the different results considering the link between positive symptoms and violent behaviour in FEP (Brucato et al, 2019;Coid et al, 2013;Langeveld et al, 2014;Large and Nielssen, 2011) and psychotic disorders in general, where the positive symptom subscale is associated with violence (Volavka et al, 2016;Witt et al, 2013), we found hallucinations, delusions and unusual thought content low but significantly associated with hostility and disturbing and aggressive behaviour.…”
Section: Discussionmentioning
confidence: 91%
“…For the analysis of clinical factors associated with hostility, we selected seven PANSS items to see if these are related to PANSS P7 and PSP-D. We included the four PANSS items that are in the Excitement Component (PANSS-EC), along with hostility: P4 excitement, G14 poor impulse control, G4 tension and G8 uncooperativeness (Montoya et al, 2011). Impulsivity was associated with violence in FEP (Moulin, Golay, et al, 2018) and more chronic populations (Faay et al, 2020), but for excitement, tension and uncooperativeness, there is lacking evidence in a population of FEP. Next to these items, we wanted to examine whether delusions and hallucinations are associated with hostility or aggression because of the contrasting results from previous studies (Brucato et al, 2019;Coid et al, 2013;Langeveld et al, 2014;Large & Nielssen, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation